Role of mental state explanations in children’s theory of mind development. - Chee, Yu Yan. (2013)
Theory of Mind (ToM) is the ability to take others’ desires, needs and knowledge into account. This is an essential ability for children to develop during preschool years. The current study employed a guided role-play intervention programme to investigate the role of adult-guidance and other factors such as language and executive function involved in children’s ToM development. Preschoolers (N = 26) were randomly assigned to either the guided role-play condition or the non-guided role-play condition. In the guided role-play condition, pre-schoolers received feedback and guidance from trainers who encouraged them to provide psychological explanations to false belief situations. In the non-guided condition, pre-schoolers did not receive any active guidance from the trainers. Measures used to quantify receptive ability, and executive function (working memory and cognitive flexibility) include the Peabody Picture Vocabulary Test (PPVT), the Flexible Item Selection Test (FIST), and the backward digit span. Results from the study indicated that children in the guided-role-play condition outperform the children in the non-guided role-play condition in ToM tasks. Additionally, working memory is shown to be linked to gain in ToM scores. The present data provided support that adult guidance through the provision of providing psychological explanations are important in helping children to improve their ToM abilities. It had also been determined that working memory is the underlying cognitive mechanism.